Intraventricular Ganglioglioma Presenting with Spontaneous Hemorrhage - Campos, AR (2018)
Intraventricular gangliogliomas presenting with spontaneous hemorrhage are rare. Due to high density of important tracts lateral to the ventricular atrium, the intraparietal trans sulcal approach is a good option to remove lesions in this location. These tracts are displaced and sometimes destroyed by the presence of large masses. A 33-year-old male presented with a sudden headache and a generalized seizure. He had a left visual field hemianopia and left visual field neglect. Brain computer tomography and magnetic resonance imaging revealed a hemorrhagic tumor located in his right atrium. With the help of tractography an optimal corridor to the tumor through the intraparietal sulcus was planned. Gross total removal of a ganglioglioma was possible with recovery of visual impairment and control of epilepsy. The efficacy in using tractography as a planning tool for safe tumor removal is demonstrated with clinical, imagiological and histological data, and a surgical video.